Activation of a Cell Surface Signaling Pathway in Pseudomonas aeruginosa Requires ClpP Protease and New Sigma Factor Synthesis - Bishop, Thomas F.; Martin, Lois W.; Lamont, Iain L. (Frontiers in Microbiology, 2017)
Extracytoplasmic function (ECF) sigma factors control expression of large numbers of genes in bacteria. Most ECF sigma factors are inhibited by antisigma proteins, with inhibition being relieved by environmental signals that lead to inactivation of the antisigma protein and consequent sigma factor activity. In cell surface signaling systems in Gram negative bacteria antisigma activity is controlled by an outer membrane protein receptor and its ligand. In Pseudomonas aeruginosa one such system controls expression of genes for secretion and uptake of a siderophore, pyoverdine. In this system the activities of two sigma factors σFpvI and σPvdS are inhibited by antisigma protein FpvR20 that binds to the sigma factors, preventing their interaction with core RNA polymerase. Transport of ferripyoverdine by its outer membrane receptor FpvA causes proteolytic degradation of FpvR20, inducing expression of σFpvI - and σPvdS-dependent target genes. Here we show that degradation of FpvR20 and induction of target gene expression was initiated within 1 minute of addition of pyoverdine. FpvR20 was only partially degraded in a mutant lacking the intracellular ClpP protease, resulting in an FpvR20 subfragment (FpvR12) that inhibited σFpvI and σPvdS. The translation inhibitor chloramphenicol did not prevent induction of an σFpvI -dependent gene, showing that degradation of FpvR20 released pre-existing σFpvI in an active form. However chloramphenicol inhibited induction of σPvdS-dependent genes showing that active σPvdS is not released when FpvR20 is degraded and instead, σPvdS must be synthesized in the absence of FpvR20 to be active. These findings show that sigma factor activation occurs rapidly following addition of the inducing signal in a cell surface signaling pathway and requires ClpP protease. Induction of gene expression that can arise from release of active sigma from an antisigma protein but can also require new sigma factor synthesis.